2017
DOI: 10.18632/oncotarget.16688
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin state dynamics during NK cell activation

Abstract: Studies of Natural Killer (NK) cell cytotoxicity have mainly focused on the balance of activating and inhibitory receptors, signaling transduction, calcium influx, formation of immune synapse, and cytolytic degranulation. However, little is known about the chromatin state of NK cells and the impact of its changes during target recognition. In this study, we investigate the contribution of chromatin state dynamics during NK cell activation by comprehensively analyzing a set of microarray data and two sets of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Inhibition of IL-12 production is an important part of the immune evasion mechanism of T. gondii [48]. TNFSF9 was confirmed to play important roles during NK and B cell activation [49, 50]. Therefore, the differences in the expression patterns of cytokines regulated by miRNAs that we observed at 10 and 50 DPI may be due to differences in the host immune responses induced by acute and chronic T. gondii infections.…”
Section: Discussionmentioning
confidence: 90%
“…Inhibition of IL-12 production is an important part of the immune evasion mechanism of T. gondii [48]. TNFSF9 was confirmed to play important roles during NK and B cell activation [49, 50]. Therefore, the differences in the expression patterns of cytokines regulated by miRNAs that we observed at 10 and 50 DPI may be due to differences in the host immune responses induced by acute and chronic T. gondii infections.…”
Section: Discussionmentioning
confidence: 90%
“…NK cells are typically activated and more cytotoxic in presence of IFNc, which induces trained immunity [104]. These characteristics can be enhanced by EZH2 inhibition [105,106], as well as BET inhibition that induces NK activating ligands and receptors [55]. Cytokines such as IFNc, IL4 and IL1 will determine the macrophage behaviour towards tumours cells (either protective or cytotoxic).…”
Section: Nk Cellsmentioning
confidence: 99%
“…Moreover, using a combination of microarray and ChIP-sequencing analysis, Li et al found that NK cell activation of the NK-92MI cell line is characterized by dynamic changes in the expression of HDM and HMT as well as changes in H3K27me3 and H3K4me3 and specific loci. Inhibition of H3K27me3 using UNC-1999 resulted in increased degranulation capacity of NK cells ( 159 ).…”
Section: The Immune Cell Epigenome In the Cancer Microenvironmentmentioning
confidence: 99%